Derechos sociales y orden internacional (2019)
Social rights are a product of human needs and under these has been developed in history as demands which were subsequently accepted by the national law in their constitutions and then, as a result of the global dynamic, in norms of international law, where they are also stablished institutions to which citizens can turn to force the state to fulfill some of these guarantees or compensate damages. On the other hand, the States for they operation adopt economic models and in this way take a position on their role in society. Thus, for decades the neoliberal economic model has been prevailing in national policies, thanks to pressure from the major capital through the global powers and international financial institutions, impacting negatively the effectiveness of social rights. In this context, the article, from the historical analysis of social rights and the study of the new international order, analyzes the role of these rights today.